Development of STEM-Based Project Learning Tools Integrating Local Wisdom of the Gendang Melayu on the Topic of Sound Waves - Musyaddad, Muhammad; Pathoni, Haerul; Alrizal, Alrizal (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to assess the feasibility of developing STEM-integrated Project-Based Learning (PjBL) tools incorporating the local wisdom of Gendang Melayu for the topic of sound waves. The development followed the 4D model and was limited to the development stage. In the define phase, several analyses were conducted, including initial-final, learner, task, concept, and learning objectives. The design phase structured the lesson plan (RPP) and student worksheet (LKPD) formats based on PjBL syntax and STEM components. During the development stage, the RPP and LKPD were validated by two expert lecturers and one physics teacher. The RPP scored 94.11% and 91.76%, while the LKPD scored 94% and 95%, all categorized as